2017
DOI: 10.1038/s41598-017-09575-6
|View full text |Cite
|
Sign up to set email alerts
|

The conserved tyrosine residue 940 plays a key structural role in membrane interaction of Bordetella adenylate cyclase toxin

Abstract: The adenylate cyclase toxin-hemolysin (CyaA, ACT or AC-Hly) translocates its adenylate cyclase (AC) enzyme domain into target cells in a step that depends on membrane cholesterol content. We thus examined what role in toxin activities is played by the five putative cholesterol recognition amino acid consensus (CRAC) motifs predicted in CyaA hemolysin moiety. CRAC-disrupting phenylalanine substitutions had no impact on toxin activities and these were not inhibited by free cholesterol, showing that the putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 64 publications
2
35
0
Order By: Relevance
“…Previous studies of other RTX toxins, namely the B. pertussis toxin CyaA 22 24 , the E. coli α-hemolysin HlyA 25 , 26 and the A. actinomycetemcomitans leukotoxin LtxA 27 , demonstrated that they are post-translationally activated through amide-linked fatty acylation of the ε-amino groups of two conserved internal lysine residues. Sequence alignment analysis of these three RTX toxins with RtxA revealed lysine residues 558 and 689 of proRtxA to be putative acylation sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of other RTX toxins, namely the B. pertussis toxin CyaA 22 24 , the E. coli α-hemolysin HlyA 25 , 26 and the A. actinomycetemcomitans leukotoxin LtxA 27 , demonstrated that they are post-translationally activated through amide-linked fatty acylation of the ε-amino groups of two conserved internal lysine residues. Sequence alignment analysis of these three RTX toxins with RtxA revealed lysine residues 558 and 689 of proRtxA to be putative acylation sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is generally accepted that the RTX toxins are post-translationally acylated on the ε-amino groups of two conserved lysine residues, the type of acyl chains has only been experimentally identified for three RTX toxins, namely the B. pertussis CyaA 22 24 , the E. coli α-hemolysin HlyA 25 , 26 and the A. actinomycetemcomitans leukotoxin LtxA 27 . Analysis of the predicted acylated segment of RtxA and its alignment with the corresponding regions of CyaA, HlyA and LtxA revealed that the RtxA protein contains two conserved lysine residues, K558 and K689 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobic pore-forming domain of CyaA, comprised between residues 500 to 700 ( Figure 1 ), consists of several predicted amphipathic and hydrophobic α-helical structures. These play a key role both in AC domain translocation, as well as in the formation of cation-selective oligomeric CyaA pores within target membranes [ 11 , 19 , 25 , 66 , 67 , 68 , 69 ]. By using the method of osmotic solute exclusion, the size of the pore formed by CyaA in the cell membrane was estimated to be between 0.6 to 0.8 nm in diameter [ 26 ].…”
Section: Cyaa Structurementioning
confidence: 99%
“…An “AC-to-Hly-linking” segment of CyaA was identified and its arginine residues appear to be involved in the disruption of the membrane bilayer, which enables insertion and translocation of the AC domain of CyaA across the plasma membrane of cells [ 5 , 6 , 7 ]. Furthermore, the structural integrity of the putative transmembrane helices I, III, and IV of the hydrophobic domain was shown to be essential for AC domain translocation across the plasma membrane of both CD11b + and CD11b − cells [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%